Strategi Pendidikan Life Skills di Pondok Pesantren al-Muhajirin 1 Bahrul Ulum Tambakberas Jombang - Hasan, Muhammad Zainul; Waslah; Huda, Saihul Atho' Alaul (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2023)
The research began with the observation of many graduates from Islamic boarding schools (pesantren) who still lacked self-confidence after completing their education. The aim of the Life Skills Education Strategy for Students at Al-Muhajirin 1 Bahrul Ulum Tambakberas Jombang Islamic Boarding School was to determine the strategies used in providing life skills education and the supporting and hindering factors in its implementation at the Islamic boarding school. The research employed a qualitative approach, involving methods such as observation, interviews, and document analysis with caregivers, teachers (ustadz), and the students themselves as the research subjects. Data analysis was conducted through triangulation, involving data reduction, data presentation, and drawing conclusions. The research findings are as follows: Vocational skills education through Cooperative Pondok activities aimed to enhance entrepreneurial skills. Social skills education through Security and Order and Roan activities aimed to improve social skills, cooperation, and effective communication among students. Academic skills education through Khitobah activities aimed to develop public speaking skills and self-presentation. As for the supporting and hindering factors: In vocational skills education, students were enthusiastic about participating in the cooperative, but a hindering factor was the prevalence of student debt. In social skills education, the management recognized the importance of responsibility and supervision, but a hindrance was the lack of discipline, and sometimes the management struggled to maintain order among the students. In academic skills education, students were enthusiastic about creating Khitobah presentations, but a hindering factor was their lack of self-confidence.